Basel III, capital stability, risk-taking, ownership: Evidence from Asia - Pichaphop Chalermchatvichien (2018)
© 2014 Elsevier B.V. This study investigates the associations among bank risk-taking, ownership concentration, and the recently proposed standard for capital stability (Basel III). Consistent with theory, the evidence shows that a rise in ownership concentration by one standard deviation increases the extent of risk-taking by as much as 6-8%. Although Basel III does not start taking effect until 2013, we hypothetically apply the capital stability standard on a sample of East Asian banks in the period 2005-2009. Our results suggest that an improvement in capital stability by one standard deviation diminishes the extent of risk-taking by 5.37% (as measured by the bank's Z-score). We also find that the standard for capital stability would have been more effective in countries with better economic development. Our results provide insights into the likely effects of Basel III and should be useful to a wide range of audiences, including policymakers, regulators, bankers, as well as practitioners and researchers.